Effect of short-term heat treatment in the hydrogen on magnetic properties of ZnO:Mn nanocrystals - Kovalenko, O.V.; Vorovsky, V.Yu.; Khmelenko, O.V.; Kushnerov, O.I. (Physics and Chemistry of Solid State, 2022)
The magnetic properties of ZnO:Mn(2at%) nanocrystals synthesized by ultrasonic aerosol pyrolysis were studied. It has been established that short-term thermal treatment in hydrogen does not affect the magnetization of the synthesized sample, which had ferromagnetic and paramagnetic components. The sample, which underwent heat treatment in air at T = 850°C and acquired paramagnetic properties, after heat treatment in hydrogen again became ferromagnetic without a paramagnetic phase. It has been established by the EPR method that the structure of defects in the synthesized ZnO:Mn(2%) NCs is inhomogeneous. It changes after heat treatment in hydrogen. It is shown that the controlled thermal treatment of the samples, first in air and then in hydrogen, makes it possible to predictably change their magnetic properties. The results obtained are explained using the model of coupled magnetic polarons. During thermal treatment in hydrogen, the ratio of the number of oxygen vacancies Vo and interstitial Mn2+ ions changes in the samples.